Postharvest wounding treatment influences flavone production and biological activities of the hairy root cultures of Scutellaria baicalensis - Hyeon Ji Yeo; Su Young Shin; Sang Un Park; Chang Ha Park (Chemical and Biological Technologies in Agriculture)
Abstract Background Scutellaria baicalensis roots contain root-specific flavones (baicalin, baicalein, and wogonin) exhibiting strong biological effects. Hence, this plant is considered the best plant material for hairy root system applications. Results In this study, we obtained hairy roots, which are considered natural genetically modified organisms, from S. baicalensis leaves in vitro using wild Agrobacterium rhizogenes (A. rhizogenes) R1000 and investigated the effects of postharvest wounding treatment on their flavone production and in vitro antimicrobial properties. Hairy roots were exposed to wounding stress, and the levels of baicalin, baicalein, and wogonin were determined using high-performance liquid chromatography (HPLC). We found that the levels of these flavones in S. baicalensis hairy roots increased after 6, 12, 24, 48, 72, and 96 h of exposure in a time-dependent manner. In particular, the highest production of three flavones was reported after exposure to 96 h of wounding stress. Furthermore, the expression levels of genes involved in root-specific flavone pathways (SbPAL1, SbPAL2, SbPAL3, SbCCL7, SbCHS2, SbCHI, SbFNS2-2, SbCYP82D1.1, and SbF8H) were determined at two time points (control and after 96 h of exposure). Expression levels of SbPAL1, SbCHS2, SbCHI, and SbCYP82D1.1 were significantly increased following exposure to wounding stress. Antimicrobials were observed with seven normal pathogens, two multidrug-resistant pathogens, and one pathogenic yeast. Moreover, the inhibition zone sizes of these bacteria were larger in the wounded S. baicalensis hairy roots with higher levels of baicalin, baicalein, and wogonin than in those with lower levels of these flavones. In addition to antimicrobial activities, the wounded hairy roots exhibited stronger anti-inflammatory and antioxidant activities than the controls. Conclusions Our results indicate that postharvest wounding treatment is a good strategy to increase flavone production and enhance the antibacterial activity of S. baicalensis hairy root cultures. Graphic Abstract